FANALISA KEBUTUHAN KALSIUM KARBID PADA PROSES DE-SULFURISASI PEMURNIAN NIKEL FENI II PADA PT ANEKA TAMBANG, TBK UBPN SULTRA PROVINSI SULAWESI TENGGARA - Rembah, Rina (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Aneka Tambang Tbk UBPN SULTRA was the once company of nation under order of BUMN (Badan Usaha Milik Negara) consentration in mining nickel, in place At Kecamatan Pomalaa, Kabupaten Kolaka South East Provence. Two factory was operated since 1975 with capacity 11.000 ton nickel/year, however once factory was builded since 1995 with capacity 24.000 ton nickel/year and after that production since 2004 with cost assumption 200 U$$. One of step process smelter to up the ferronickel grade is refining process. And to down sulfur grade in product so that accept standart product in market â‰¤ 0,03%, that do it de-sulfurisasi process. The problem in refining process specialy de-sulfurisasi refining is over consumption calcium cabid, long time process that down the temperature and grade in product not accept in international market.From result of calculated consumption calsium cardib for de-sulfurisasi proces as we know that rate consumption for assosiated 1 kg sulfur need 3, 69 kg calsium cardib. And to reduce consumption between planning and realitation is 40,39 kg/tapping proces. Rate temperature need is 2oc/minute for once tapping proces and need time to proces is 37 minute.rate Down temperature for once proces is 74,2oc, rate of consumption calsium carbid pertapping is 489,6 kg. Factorâ€™s efect in comsumption calsium carbid is condition of ladle, temperatur,stirer condition, mechanisem into material in ladle and specialy of operator.